Tenses, Voices, and Moves in the ELT Research Abstracts: A Corpus-based Study - Achmad Kholili (Masters in English Education, The Directory of Postgraduate Program,Universitas Muhammadiyah Malang, 2022)
In writing a research paper, the writers will, of course, include a concise report or the so[1]called abstract to pass on information to the readers concerning their studies. The problems not only arise in presenting an idea in reporting the study but also have trouble using grammatical structures and patterns established in the abstract they write. To this effect, this study was conducted to investigate elements used in the abstracts of ELT Journal. The aim of this study was to provide the researchers with the proper guideline in writing abstracts appropriately. The twelve journals ranging from 2015 to 2018 publications were selected to analyze with respect to tenses, voices, and move structures employed in the abstracts. Swales & Feak’s (2004) move structures were adopted in this study so as to analyze the moves in the abstracts. The findings of the study show variations with regard to tenses, moves, and voices used in the abstracts. In tenses, introduction and results of the study employed present tense, whereas past tense was frequently used in aims, methods, and results. In the meantime, in terms of voice, four moves showed active voices in the abstracts including Move 1, Move 2, Move 4, and Move 5 in spite of the fact that Move 3 used passive voice. Furthermore, the rhetorical move following Swales & Feak’s (2004) only certifies 8.3 %. In other words, only 1 article abstract followed it, whereas others demonstrated variation in moves. This finding makes a substantial contribution to the writers, especially for the novice writers in an ELT research context.